2015
DOI: 10.1155/2015/865986
|View full text |Cite
|
Sign up to set email alerts
|

Chronic Treatment with a Water-Soluble Extract from the Culture Medium ofGanoderma lucidumMycelia Prevents Apoptosis and Necroptosis in Hypoxia/Ischemia-Induced Injury of Type 2 Diabetic Mouse Brain

Abstract: Type 2 diabetes mellitus has been known to increase systemic oxidative stress by chronic hyperglycemia and visceral obesity and aggravate cerebral ischemic injury. On the basis of our previous study regarding a water-soluble extract from the culture medium of Ganoderma lucidum mycelia (designed as MAK), which exerts antioxidative and neuroprotective effects, the present study was conducted to evaluate the preventive effects of MAK on apoptosis and necroptosis (a programmed necrosis) induced by hypoxia/ischemia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(11 citation statements)
references
References 52 publications
(88 reference statements)
0
11
0
Order By: Relevance
“…Several types of harmful stimuli alter the permeability of mitochondrial membrane to reduce membrane potential, block transmission of mitochondrial electron transport chain, suppress cytochrome c production, inhibit adenosine triphosphate (ATP) level, accelerate ROS accumulation, promote local inflammatory cell infiltration and eventually lead to necroptosis . Some studies have confirmed that there was more serious necroptosis in the brain of type 2 diabetic mice than that of non‐diabetic mice . Necroptosis was also enhanced in cardiomyocytes after high‐glucose stimulation .…”
Section: Discussionmentioning
confidence: 99%
“…Several types of harmful stimuli alter the permeability of mitochondrial membrane to reduce membrane potential, block transmission of mitochondrial electron transport chain, suppress cytochrome c production, inhibit adenosine triphosphate (ATP) level, accelerate ROS accumulation, promote local inflammatory cell infiltration and eventually lead to necroptosis . Some studies have confirmed that there was more serious necroptosis in the brain of type 2 diabetic mice than that of non‐diabetic mice . Necroptosis was also enhanced in cardiomyocytes after high‐glucose stimulation .…”
Section: Discussionmentioning
confidence: 99%
“…Temporal changes in systemic oxidative stress of each group were assessed by measuring the serum levels of hydroperoxide just before and 24, 72 h, and 14 days after 2VO using an active oxygen-free radical autoanalyzer (Free Radical Elective Evaluator: F.R.E.E., Grosseto, Italy) and the d-ROMs test kit as previously reported [43]. The results of the d-ROMs test were expressed in arbitrary units called “Carratelli units” (U. CARR), where 1 U. CARR corresponds to 0.08 mg/100 mL H 2 O 2 .…”
Section: Methodsmentioning
confidence: 99%
“…Intracellular O 2 − generation induced by 2VO in the striatum was detected by DHE staining [43]. Coronal brain sections (30-µm thick) were incubated with DHE (10 µmol/L, Sigma-Aldrich, St. Louis, MO, USA) in 10 mM phosphate-buffered saline (PBS, pH 7.4) for 30 min at 37 °C.…”
Section: Methodsmentioning
confidence: 99%
“…Brain hypoxia often causes severe changes to the internal and external environments of cells, often leading to necrosis or apoptosis and also often activating self-repair mechanisms in response to hypoxic injury ( 14 , 15 ). Recently, although neuronal apoptosis has been well documented at the molecular level, the mechanism remains unknown and the chaos of apoptosis may be closely associated with the genesis and development of multiple nervous system diseases, such as stroke ( 16 , 17 ), cerebral injury ( 18 , 19 ), neurologic tumors and neurodegenerative recession diseases ( 20 23 ).…”
Section: Introductionmentioning
confidence: 99%